Complex Appraisal of Quality of Life on Regional Level - O. E. Nikonets (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The topic of the article is investigation of methods used to estimate the quality of life with due regard to regional specific features. The goal of the research is to study the process of altering the ‘quality of life’ definition and to analyze the current methods of appraising quality of life in regions of the Russian Federation in view of finding the dependence between level of social welfare and satisfaction with high standard of quality of life. The article analyzes origin of the notion ‘quality of life’, studies world and Russian practices of estimating the quality of life index in present day conditions and identifies principles of shaping the key indicators of appraisal. The author analyzed experience of the rating assessment of quality of life by Russian and overseas agencies and academic associations. The analysis showed that key elements of indicators take into account such trends as the level of region development, natural and climatic conditions, level of people income, social sphere and labour market. The use of numerous criteria can give an opportunity to obtain an accurate and truthful assessment on the regional level. Factors provided in the article show the necessity to develop uniform approaches on theoretical and methodological levels based on human-centric principles, which can become a key indicator of the general appraisal of social and economic development of regions and a tool of strategic planning.